2012
DOI: 10.1103/physreve.85.056202
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to surrogate data methods for nonstationary time series

Abstract: The method of surrogate data has been extensively applied to hypothesis testing of system linearity, when only one realization of the system, a time series, is known. Normally, surrogate data should preserve the linear stochastic structure and the amplitude distribution of the original series. Classical surrogate data methods (such as random permutation, amplitude adjusted Fourier transform, or iterative amplitude adjusted Fourier transform) are successful at preserving one or both of these features in station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In order to make the results more reliable, particularly in the case of nonstationary EEG signals, we also use the truncated Fourier transform (TFT) surrogates proposed by Nakamura et al [35]. TFT surrogates are particularly useful in preserving some nonstationarity present in the original data in the surrogates, unlike the iAAFT surrogates which can only preserve the linear properties [35,36]. Particularly, we test for randomness based on network measures, the average clustering coefficient C, assortativity R, the average path length L, and the average betweenness centrality BC and independence based on crossnetwork measure, the average cross-clustering coefficient C cross in the focal and nonfocal EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…In order to make the results more reliable, particularly in the case of nonstationary EEG signals, we also use the truncated Fourier transform (TFT) surrogates proposed by Nakamura et al [35]. TFT surrogates are particularly useful in preserving some nonstationarity present in the original data in the surrogates, unlike the iAAFT surrogates which can only preserve the linear properties [35,36]. Particularly, we test for randomness based on network measures, the average clustering coefficient C, assortativity R, the average path length L, and the average betweenness centrality BC and independence based on crossnetwork measure, the average cross-clustering coefficient C cross in the focal and nonfocal EEG signals.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, in this work, we are interested in analyzing the advantages of using decomposition methods to produce surrogate data regardless of the presence of nonstationary behavior. A comparative study among those methods can be found in [Maiwald et al, 2008;Schreiber & Schmitz, 1996;Lucio et al, 2012].…”
Section: Surrogate Methodsmentioning
confidence: 99%
“…The TFTS method was later considered by Lucio et al [2012], who presented two new techniques named AAFT TD and IAAFT TD . Similarly to our approach, the authors designed these techniques to preserve the global nonstationarity present in time series.…”
Section: Surrogate Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved version of the AAFT algorithm has been suggested by Schreiber and Schmitz [8,9] using an iterative scheme called the IAAFT surrogates, which is reported to be more consistent to test null hypothesis [7]. Recently, Nakamura et al [10] have proposed a surrogate generation method called Truncated Fourier Transform (TFT) [11]. However, the surrogate data generated by this method are influenced by a cut-off frequency.…”
Section: Introductionmentioning
confidence: 99%